STUDI PERILAKU LEBAH KELULUT Tetragonula fuscobalteata (APIDAE: MELLIPONINAE) DALAM MENEMPATI SARANG KOTAK BARU - Saud, Oshlifin Rucmana; Harmonis, Harmonis; Saud, Oshferlia Rucmana; Utami, Widia Sri (MAKILA, 2024)
Kelulut bees have different habits when building nests between species. Tetragonula fuscobalteata is a type of the kelulut bee that is widely cultivated. Collecting bee colonies is generally carried out using various techniques, including nest dismantling, grafting, and bait techniques. Much research has been conducted on broodstock of kelulut bees, such as colony propagation techniques and the use of nest grafting methods, but research on the behavior of placing kelulut bee colonies in new nest boxes, especially on the T. fuscobalteata species, has never been carried out and done a lot. Therefore, this study aims to provide data regarding the behavior of placing T. fuscobalteata kelulut bee colonies in new nest boxes and measuring the temperature and humidity in new nest boxes sprayed with propolis extract liquid. This research used a direct observation method on new nest boxes that had been sprayed with propolis extract, and propolis was attached to the box entrance hole. The results showed that the movement behavior of the T. fuscobalteta bee colony from the old nest to the new nest occurred on the third day after repairing the nest and building the nest in the form of making honey bags, eggs, and bees. Bread occurs for 5 days. The ideal temperature in the nest is between 27.7 0C-29.70C, and the ideal humidity is between 70%-80%. The results of this research can be a reference for kelulut honey bee breeders, especially the T. Fuscobalteata, about the propagation of kelulut bee colonies